Quality of life of Families of Persons with Sensory Disabilities: Problems and Adaption Mechanisms Researchers - Al-Ghamdi, Samaher Ahmad; Al-Gurashi, Reham Hassan; Al-Qahtani, Rajaa Taha (Journal of Humanities & Social Sciences, 2024)
The family is the corner stone upon which societies are built, but it may face challenges such as the presence of a person with a disability, which has to face and adapt to these challenges. The study analyzed these problems and coping mechanisms using the role theory and stigma theory. The study adopted the blended approach using electronic questionnaire for (125) families and semi-structured interviews for (9) families with disabilities. The study has concluded: That the presence of a child with special needs brings the family members closer and increases their cooperation. The family started treatment as soon as they found out that they had a child with special needs. The family does not face any social issues with presence of a disabled person, and there are no psychological issues either. The person with the disability is treated as normal as other members of the family, and the family believes that having a child with special needs is a gift from Allah that he gives to his patient believers. The main issues that face families with a disabled child are: The lack of services in public spaces, there are no specific entities that provides awareness to the families about the rights and services available for people with special needs, that caring for a disabled person can cause a lot of psychological pressure, and that the costs needed to treat the disabled person puts a big financial burden on the family. That the financial support provided for them do not cover their needs. The families think that the special needs centers do not provide all learning tools for the disabled. The most prominent adaptive mechanism to deal with these problems: The families are in constant search for modern medical treatments to deal with the problems people with disabilities face, the family treat the disabled member equally with no prejudice, the family are content and have adapted to the presence of the disabled person, the family benefits from the educational help provided for the person with special needs.